Evaluation of Effective Saturation of Air-NLAPL on the Basis of Air-Water Tests in Soils with Multimodal Pore-Size Distribution - Alfaro Soto, Miguel A. [UNESP]; Kiang, Chang H. [UNESP]; Dos Santos, Eduardo P. [UNESP] (American Society of Civil Engineers (ASCE), 2018)
This paper was designed to verify if effective saturation distribution for air-LNAPL systems obtained indirectly as suggested by the American Petroleum Institute (2007) are adequate for soils of lateritic nature found in various territories of Brazil. The effective saturation of air-water systems were determined using hanging column tests for typical samples of the state of Satild;o Paulo (Brazil). These results were then compared to the effective saturations obtained in similar tests for air-LNAPL systems. In both cases, the capillary pressure curves were typical of soils with multimodal pore-size distribution. Moreover, indirect models for effective saturation curves of air-LNAPL were coherent, as long as a tri-modal model was used. Further studies for the prediction of the specific volumes of contaminants in tropical soils are recommended due to the differential retention characteristics.